2020
DOI: 10.1021/acsami.9b23389
|View full text |Cite
|
Sign up to set email alerts
|

Control of Circular Photogalvanic Effect of Surface States in the Topological Insulator Bi2Te3 via Spin Injection

Abstract: The circular photogalvanic effect (CPGE) provides a method utilizing circularly polarized light to control spin photocurrent and will also lead to novel opto-spintronic devices. The CPGE of three-dimensional topological insulator Bi 2 Te 3 with different substrates and thicknesses has been systematically investigated. It is found that the CPGE current can be dramatically tuned by adopting different substrates. The CPGE current of the Bi 2 Te 3 films on Si substrates are more than two orders larger than that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…These samples have been shown to mimic truly the robust helical surface states. , A detailed study of the photocurrent response for different polarization states of excitation light beam under ambient conditions allowed us to differentiate between surface and bulk contributions. Measurements with variation of the angle of incidence of the excitation beam reveal the microscopic origin of different components of the helical photocurrent, such as the circular photogalvanic effect and the linear and circular photon drag effects. , Our experimental observations match well with previously reported theoretical proposals. Having confirmed the existence of surface states and their contribution to the photocurrent, we have shown that the helical photocurrent can also be tuned with the help of thermal gradient produced by the excitation beam.…”
Section: Introductionsupporting
confidence: 87%
“…These samples have been shown to mimic truly the robust helical surface states. , A detailed study of the photocurrent response for different polarization states of excitation light beam under ambient conditions allowed us to differentiate between surface and bulk contributions. Measurements with variation of the angle of incidence of the excitation beam reveal the microscopic origin of different components of the helical photocurrent, such as the circular photogalvanic effect and the linear and circular photon drag effects. , Our experimental observations match well with previously reported theoretical proposals. Having confirmed the existence of surface states and their contribution to the photocurrent, we have shown that the helical photocurrent can also be tuned with the help of thermal gradient produced by the excitation beam.…”
Section: Introductionsupporting
confidence: 87%
“…24,26 Under illumination by a circularly polarized light with certain helicity, the resulting CPGE current is a superposition of electron current and hole current, which propagates along the same direction but with an opposite sign. 31,39 Therefore, electron current and hole current tend to cancel each other in each single valley. In this SL-MoS 2 /FL-MoS 2 homojunction, the band alignment enables holes to undergo ultrafast transfer from SL-MoS 2 to FL-MoS 2 due to the relatively large valence band offset between them, while electron transfer can be neglected.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The possible underlying mechanism of this enhanced CPGE current in the homojunction device under on-resonance and quasi-resonance excitation is schematically shown in Figure e. Owing to the valley-dependent optical selection rule in SL-MoS 2 , σ+/σ– circularly polarized light can only excite the carriers at the K/K′ valley, which thus leads to the valley population imbalance. , Under illumination by a circularly polarized light with certain helicity, the resulting CPGE current is a superposition of electron current and hole current, which propagates along the same direction but with an opposite sign. , Therefore, electron current and hole current tend to cancel each other in each single valley. In this SL-MoS 2 /FL-MoS 2 homojunction, the band alignment enables holes to undergo ultrafast transfer from SL-MoS 2 to FL-MoS 2 due to the relatively large valence band offset between them, while electron transfer can be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, by replacing the SrTiO 3 substrate by Si wafer, the CPGE current of Bi 2 Te 3 films was also found to be significantly improved by two orders of magnitude, profiting from the extra spin injection from Si substrate to TI. [ 213 ] However, the surface states observation is often mixed with non‐negligible contribution from the bulk states in conventional transport experiments. To tackle this issue, Kastl et al.…”
Section: Quasi‐2d Topological Materialsmentioning
confidence: 99%
“…In addition, by replacing the SrTiO 3 substrate by Si wafer, the CPGE current of Bi 2 Te 3 films was also found to be significantly improved by two orders of magnitude, profiting from the extra spin injection from Si substrate to TI. [213] However, the surface states observation is often mixed with non-negligible contribution from the bulk states in conventional transport experiments. To tackle this issue, Kastl et al [214] isolated ultrafast helicity-dependent currents of TSSs in Bi 2 Se 3 film from laser heating-induced thermoelectric currents and drift currents in the bulk on a picosecond timescale by time-resolved and timeintegrated photocurrent spectroscopy.…”
Section: Circular Photogalvanic Effectmentioning
confidence: 99%